Nonlinear Noise Compensation in an Integration System of Fiber-Wireless Communication and Free Space Optical Communication - Long Chen; Miao Liu; Zhijun Tang (Advances in Condensed Matter Physics)
We propose and experiment an integration system of fiber-wireless communication and free space optical (FSO) communication based on nonlinear noise compensation. This integration system, combining the benefits of FSO communication and high-frequency wireless communication, as well as the high-frequency efficiency and anti-interference to multipath fading of the multicarriers orthogonal frequency division multiplexing (OFDM) modulation, can increase the capacity and flexibility of the system. The nonlinear equalizer is employed to compensate the distortion caused by the beating between OFDM signal subcarriers in the combination system. Up to 1-Gbaud 16QAM discrete multitone (DMT) OFDM signal can be first transmitted over the distance of 100-m single-mode fiber (SMF), then delivered over the distance of 100-m FSO link, and finally, transmitted over the distance of 4 m wireless. The bit-error-ratio (BER) of the OFDM signal in the integration system can be less than the hard-decision forward-error-correction (HD-FEC) threshold of 3.8 × 10−3. The experiment shows that the nonlinear equalizer can work well compatible with the combination system and can improve the transmission performance by 0.7-dB receiving sensitivity in the combination system.